Psychological Distress, Mental Health Stigma and Help Seeking Behavior in University Students - Saima Ahmad; Aania Tasheeh; Rameesha (PJPPRP, 2026)
The purpose of this study is to explore the association among psychological distress, mental health stigma and help-seeking behavior in university students. For this purpose, a correlational cross-sectional study was designed. The study was conducted at three universities of Lahore i.e. Lahore College for Women University, Government College University, and Kinnaird College for Women, Lahore. In the current study, 100 males and 100 females, aged 20-25 (M = 22.89, SD = 1.32), were included. Data were collected using purposive sampling. Assessments were conducted using a self-constructed demographic sheet, the Kessler Psychological Distress Scale (K10), the Stigma Scale, and the Attitude Toward Seeking Professional Psychological Help—Short Version. Different statistical techniques were used to analyze the results through SPSS. The results showed a moderate positive relationship between psychological distress and stigma of mental health, and a negative association between stigma of mental health and help-seeking behavior. Female students reported higher psychological distress and greater stigma of mental health than male students. Moreover, day scholars have higher psychological distress and stigma of mental health as compared to students living in hostels. However, no gender based or residence-based differences were observed in help-seeking behavior. Multiple regression analysis revealed that psychological distress and stigma of mental health significantly predicted help-seeking behavior, accounting for 38.0% variance.